Techniques in Teaching Vocabulary to Young Learners at LIA English Course - Ramadhani, Astuti Pratiwi (TELL - US JOURNAL, 2015)
This  study  is  attempted  to  investigate  the  specific  application  of techniques in teaching vocabulary to young learners at LIA English Course. More specifically, the research aims to 1) investigate the reality current techniques in teaching vocabulary to young learners 2) study difficulties that teachers at LIA encounter when teaching young learners vocabulary. The researchers have conducted a survey with the participation of 3 teachers from LIA English Course. Oral interviews, questionnaire and observation schemes were used as useful instruments for data collection. The questionnaire-based survey aims to reveal teachers’ common techniques in teaching vocabulary to young learners, general difficulties that they meet in teaching. Oral interviews and observations serve to elaborate the information gathered from questionnaires and discover teachers’ opinions on how to solve arisen problem in language classroom, especially during vocabulary section. The result of this study indicates that using flashcards in presenting, sorting tasks in practicing and sentence completion in revising vocabulary are three most preferably common techniques in teaching young learners vocabulary. Teachers also confirmed that they have adapted specific techniques with specific class; a combination of various ones is to be in consideration. In another aspect, most of the teachers reported that they encountered certain difficulties such as the use of too much L1, uncooperative students, students’ small attention. Nonetheless, most of the difficulties can be solved. The exploitation of combining different techniques remains rather limited; thus, this study provides some suggestions for teachers to realize the benefits of having available activities and games in young learners’ classroom.